PEDAGOGICAL AND PSYCHOLOGICAL CHARACTERISTICS OF EDUCATION OF STUDENTS IN INCLUSIVE EDUCATION (Scientific journal of the Fergana State University, 2024)
In the article, the socio-prospective importance of teaching students with disabilities in the conditions of inclusive education, pedagogical-psychological features, attitude to children covered by inclusive education based on the principles of individuality, possibilities and prospects of the processes of socialization of students, inclusive the legal basis of educational organization is described. Also, the reforms implemented in the field of inclusive education in our country and their social necessity are revealed